Radiated emission from DC bus loop of AC induction motor inverter FEM based and experimental evaluation - Kroics, Kaspars; Marks, Janis; Zarembo, Jaroslavs (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The paper describes practical method how to analyze locally radiated magnetic field to improve the geometry of printed circuit board (PCB) or busbar structure, select better control method and design electromagnetic interference (EMI) filter. Experimental prototype of three-phase induction motor variable frequency drive has been created and controlled by microcontroller with sinusoidal, namely pulse with modulation (PWM) method. Three-dimensional finite element model simulation of DC bus structure has been created and results has been obtained. Electromagnetic field was measured, practically and results compared with simulation-based ones. Simulation based and experimental results matches thus allowing to conclude method usefulness for cost effective way to test different geometries of DC bus, different modulation methods, EMI filters for variable frequency drive, and other power electronics converters.